Stability analysis of large-scale functional differential systems - Martynyuk, A.A. (Український математичний журнал, 2007)
The present paper is focused on a new method for analysis of stability of solutions of a large-scale functional differential system via matrix-valued Lyapunov-Krasovskii functionals. The stability conditions are based on information about the dynamical behavior of subsystems of the general system and properties of the functions of interconnection between them. Запропоновано один новий метод аналізу стійкості розв'язків великомасштабної функціонально-диференціальної системи на основі матричнозначного функціонала Ляпунова - Красовського. Умови стійкості ґрунтуються на динамічній поведінці підсистем загальної системи та властивостях функцій зв'язку між ними.